1981
DOI: 10.1007/bf00006319
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure as the controlling factor in the depth distribution of Eurasian watermilfoil, Myriophyllum spicatum L.

Abstract: These experimental studies have shown that this plant will grow successfully at pressures encountered in water at depths as great as 17 m. When there were suitable levels of light, temperature, nutrients and aeration, the plants grown under constant hydrostatic pressure for three weeks showed variations in the measured amounts of new growth but no measure could be associated with the constant increased hydrostatic pressure. Sudden changes in pressure are thought to play a significant role in aquatic plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…With raw soil which includes some organic matter, even at the highest hydrostatic pressure an elaborate system of air spaces will develop with time. The very active bubbling which occurred when the pressure was reduced at the conclusion of each test confirmed the previous observation (Dale, 1981). The sources of this gas are firstly from soil microorganisms and, secondly, are a product of active photosynthesis by the plant.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…With raw soil which includes some organic matter, even at the highest hydrostatic pressure an elaborate system of air spaces will develop with time. The very active bubbling which occurred when the pressure was reduced at the conclusion of each test confirmed the previous observation (Dale, 1981). The sources of this gas are firstly from soil microorganisms and, secondly, are a product of active photosynthesis by the plant.…”
Section: Discussionsupporting
confidence: 71%
“…Some problems associated with earlier tests are discussed elsewhere (Dale, 1981). This study has shown that careful planning is necessary to insure that differences in growth are due to hydrostatic pressure per se and not one of several extraneous factors such as light, gaseous exchange, soil compaction, algal competition, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants tended to elongate more in deeper water during the first week, but this was usually non-significant (Table 3). Until now, studies on the effects of hydrostatic pressure on plant growth (Gessner, 1952;Ferling, 1957;Dale, 1981Dale, . 1984 have mostly been made usmg aquatic species, and were aimed at explaining the depth distribution of these species in the field by investigating their tolerance to very high hydrostatic pressures, with effects found only at pressures similar to water depths of 5 m or more, which exceed tbe maximum depths naturally occupied by the plants under study.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sheldon & Boylen (1977) suggest that the maximum depth that plants inhabit is limited by hydrostatic pressure, Dale (1981) has shown that hydrostatic pressure has a minimal effect on the growth of milfoil in water depths up to 17 m. He feels that light, temperature, and nutrient levels are much more significant to the success of plants colonizing deep water.…”
Section: Growth Patterns Of M Spicatummentioning
confidence: 99%